Предмет: Математика,
автор: maslenkovainna308
Помогите. Нижний пример
Приложения:
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
Приложения:
Автор ответа:
1
Пошаговое объяснение:
(1 3/10 + 1/5) * 4 - 1 1/3 =
= (1 3/10 + 2/10) * 4 - 1 1/3 =
= 1 5/10 * 4 - 1 1/3 =
= 1 1/2 * 4 - 1 1/3 =
= 3/2 * 4 - 1 1/3 =
= 3 * 2 - 1 1/3 =
= 6 - 1 1/3 =
= 5 3/3 - 1 1/3 = 4 2/3
Похожие вопросы
Предмет: Физика,
автор: tdom0787
Предмет: Литература,
автор: michailkomissarov09
Предмет: Информатика,
автор: Аноним
Предмет: Математика,
автор: НичоТакПросто
Предмет: Математика,
автор: xanifa1